2013
DOI: 10.1016/j.rboe.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Is osteoarthritis a mechanical or inflammatory disease?

Abstract: Traditionally considered “wear and tear” disease, the pathogenic mechanisms of osteoarthritis have not yet been elucidated. The increasing number of articles demonstrating the influence of inflammatory factors in the onset and progression of the disease currently raises great debate in the literature about the importance of each of the factors involved in the disease. Even the choice between the terms “Osteoarthritis” and “Osteoarthrosis” generates controversy, since the first term implies the presence of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
11
0
2
Order By: Relevance
“…Cartilage loss occurs if there is excessive mechanical stress on the joint, and the creation of osteophytes is considered a reactive process of the bone to protect and stabilize the altered joint [13]. OA is a complex disease that is not purely mechanical or simply caused by in ammation; it not only involves the cartilage but also various other tissues, such as the synovium, subchondral bone, capsule, meniscus, muscle, and tendon [14]. In particular, recent research focused on the activities of hormones and cytokines related to in ammation has revealed that in addition to these mechanisms, metabolic pathways also play a large role in the development of OA [8, [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Cartilage loss occurs if there is excessive mechanical stress on the joint, and the creation of osteophytes is considered a reactive process of the bone to protect and stabilize the altered joint [13]. OA is a complex disease that is not purely mechanical or simply caused by in ammation; it not only involves the cartilage but also various other tissues, such as the synovium, subchondral bone, capsule, meniscus, muscle, and tendon [14]. In particular, recent research focused on the activities of hormones and cytokines related to in ammation has revealed that in addition to these mechanisms, metabolic pathways also play a large role in the development of OA [8, [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hira and Tamam [14], reported the mean NLR was significantly higher in the OA group than in controls. There was inconsistency about the predictive role of NLR in diagnosis, prognosis, or as a marker for disease activity for other diseases [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…There was inconsistency about the predictive role of NLR in diagnosis, prognosis or as a marker for disease activity for other diseases (15)(16)(17) .…”
Section: Discussionmentioning
confidence: 99%